Keuangan Keperilakuan (Behavioral Finance): Sebuah Overview - Mubarok, Abdulloh; Raharjo, Teguh Budi (PERMANA, 2015)
This Peper aims to overview the study of behavioral finance that comprises the concept, the difference with the standard financial and underlying theoretical framework of behavioral finance. The discussion of paper is done with the study of literature by using literature from various sources such as journals, texbook and other reference sources.The results of this peper explained that there are fundamental differences between behavioral finance and financial standards.Financial standards built on the assumption that investors are rational and markets are efficient, while behavioral finance assumes that investors are normal human beings and the market is not efficient. Behavioral finance study based on the theory of limited to arbitrage and two psychological theories, namely the theory of heuristics and prospect theory. Theory of heuristics tries to explain the various bias beliefs that affect how investors think and make decisions like anchoring, representativenes, availability bias and overconfidence. While The prospect theory tries to explain various aspects of behavioral investors in the face of financial risks such as loss aversion, mental accounting, myopic loss aversion, self-control, regret aversion. Keywords: behavioral finance, financial standards, limited to arbitrage, cognitive psychology, heuristic theory, prospect theory